Is the Separation of Powers a Useless Concept? The Components and Purpose of the Separation of Powers - Hapla, Martin (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
In this paper, the author raised the question of whether the separation of powers is a use-less concept. It points out to insufficient reflection of its theoretical and philosophical origins. The paper also distinguishes its components, which it then analyses in more detail. Great attention is dedicated to the tension between the system of checks and bal-ances and the institutional independence. It also examines the purpose of the separation of powers, warning that we can no longer seek it exclusively in the prevention of tyranny but rather in the optimization of government. At the end of the paper is emphasized the need to examine the question of how to solve tension between these components.